2019
DOI: 10.3390/cancers11030414
|View full text |Cite
|
Sign up to set email alerts
|

Chasing the FOXO3: Insights into Its New Mitochondrial Lair in Colorectal Cancer Landscape

Abstract: Colorectal cancer (CRC) poses a formidable challenge in terms of molecular heterogeneity, as it involves a variety of cancer-related pathways and molecular changes unique to an individual’s tumor. On the other hand, recent advances in DNA sequencing technologies provide an unprecedented capacity to comprehensively identify the genetic alterations resulting in tumorigenesis, raising the hope that new therapeutic approaches based on molecularly targeted drugs may prevent the occurrence of chemoresistance. Regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 157 publications
0
18
0
Order By: Relevance
“…APC mutations are present at the preliminary stages of neoplasia and are majorly linked with the classic tubular adenoma pathway and CIN cancers [ 33 , 34 , 35 , 36 ]. APC germline mutations give rise to familial adenomatous polyposis (FAP) syndrome (OMIM#: 608456), attenuated FAP, Gardner syndrome (OMIM#: 175100), Turcot syndrome (OMIM#: 276300), and other major hereditary predisposition events leading to CRC development [ 37 ].…”
Section: Molecular Basis Of Colorectal Cancermentioning
confidence: 99%
“…APC mutations are present at the preliminary stages of neoplasia and are majorly linked with the classic tubular adenoma pathway and CIN cancers [ 33 , 34 , 35 , 36 ]. APC germline mutations give rise to familial adenomatous polyposis (FAP) syndrome (OMIM#: 608456), attenuated FAP, Gardner syndrome (OMIM#: 175100), Turcot syndrome (OMIM#: 276300), and other major hereditary predisposition events leading to CRC development [ 37 ].…”
Section: Molecular Basis Of Colorectal Cancermentioning
confidence: 99%
“…Upon metabolic stress (GR), AMPK directly modulates FOXO3a functions by phosphorylating six specific FOXO3a residues [38], and growing experimental evidence suggests that other sites may also be involved [140].…”
Section: Role Of Mitochondrial Foxo3a In Cellular Stress Responsementioning
confidence: 99%
“…It has been shown that under GR conditions, AMPK promotes FOXO3a accumulation into the mitochondria of fibroblasts and skeletal myotubes, inducing the formation of a protein complex containing mtFOXO3a, SIRT3, TFAM, and mtRNA polymerase at mitochondrial DNA-regulatory regions, promoting the activation of mitochondrial gene expression and a subsequent increase in mitochondrial respiration [47,138]. Of note, AMPK can be triggered by mitochondrial ROS through an alternative pathway that involves the FOXO3a target genes MnSOD , CAT , and PGC-1α [122,140,162].…”
Section: Foxo3a-dependent Nuclear and Mitochondrial Crosstalk In Cmentioning
confidence: 99%
“…But besides that there are many studies that indicate the tumor suppressor roles of FOXO3a proteins [35,36]. Acetylation of FOXO has apoptosis promoting effect via activating the proapoptotic genes (Bim, p21, FASL6 etc) and as a result of deacetylation of FOXO3a by SIRT1 leads to cell survival and inhibition of FOXO3a mediated apoptosis [37,38]. According to our results, due to the reducing effect of 5-FU on SIRT5 expression, deacetylation of FOXO3a is alleviated and FOXO3a-dependent apoptotic pathways are induced.…”
Section: Discussionmentioning
confidence: 99%